GEEMPA methodology, a transformation in the way to alphabetize the children of first grade of primary - Hermelina Jaimes de Guerrero; Ruth Mayerly Guerrero Jaimes (Práxis Pedagógica, 2017)
GEEMPA -Grupo de estudio sobre metodología de investigación y acción (by its Spanish definition) Study Group on Research and Action Methodology- is a new flexible methodology which goal is to alphabetize a group of students in an inclusive and ludic way. The author of this methodology, Dr. Esther Pillar Grossi, states that there are no learning issues, teachers are to find new teaching strategies in accordance to the way children see the world in their early years of school life. This research looks forward to the implementation of such a methodology on early grades of primary school at Nuestra Señora del Pilar school in Pamplomita municipality -Santander-. The investigation consisted in the development of a real change in the way of teaching or orienting the learning processes; children, no matter their learning issues, were alphabetized equally. playing in the classroom was identified as a key element for achieving learning. Contests triggers a big amount of energy that could hardly be produced by conventional homework. Interviews, flash cards, game, alphabets and geempa notebooks allowed the implementation of this methodology, which produced positive results drawn from students’ learning process. Children were approached by interviewing them and analyzing psichogenesis at the end of every academic term. The latter, on its final stage, allowed positive results from their learning process.